Report on COHESA-Quadripartite joint training on One Health resources, tools, and trainings to support capacity building in the One Health workforce - Yussuf, Buke; Prasarnphanich, O.-O.; Mutua, Florence K.; Knight-Jones, Theodore J.D.; Richards, Shauna (International Livestock Research Institute, 2025)
The One Health (OH) approach recognizes the interconnection between human, animal, and environmental health, and calls for collaborative efforts across these sectors to tackle complex and emerging health threats. In Eastern and Southern Africa (ESA), however, significant gaps remain ineffective in the implementation of this approach particularly in the areas of education, workforce development, and coordination between institutions.